Paper Review on Application of Rice Hull Ash as Cement Additive: A Systematic Mapping Approach - Barra, Julianne Kate Y. (Animo Repository, 2022)
The amount of rice hull ash in the country continues to rise due to the increased consumption of rice, so utilizing methods to repurpose these wastes would be advantageous to the environment. The approximate number of rice hull wastes in the Philippines for 2021 is 3.96 million metric tons. Moreover, rice hull ash can be applied as an additive to cement because of its amorphous silica and alumina content. The performance of rice hull ash in cement can be affected by incineration under controlled temperatures. Hence, this study aims to evaluate the application of rice husk ash as cement additive through formulating a systematic mapping framework. Through this method, relevant papers were collected, organized, screened, and evaluated. The findings showed that carbonation, compressive strength, and flexural strength influence the performance of cement. The temperature and time for incineration ranges from around 260°C-1500°C for 0.25-72 hours. As a whole, the results indicate the increasing potential of rice hull ash as an additive to cement.